Temporal and compartment-specific signals coordinate mitotic exit with spindle position - Caydasi, Ayse Koca; Khmelinskii, Anton; Duenas-Sánchez, Rafael; Kurtulmus, Bahtiyar; Knop, Michael; Pereira, Gislene (Nature Communications, 2017)
The spatiotemporal control of mitotic exit is crucial for faithful chromosome segregation during mitosis. In budding yeast, the mitotic exit network (MEN) drives cells out of mitosis, whereas the spindle position checkpoint (SPOC) blocks MEN activity when the anaphase spindle is mispositioned. How the SPOC operates at a molecular level remains unclear. Here, we report novel insights into how mitotic signalling pathways orchestrate chromosome segregation in time and space. We establish that the key function of the central SPOC kinase, Kin4, is to counterbalance MEN activation by the cdc fourteen early anaphase release (FEAR) network in the mother cell compartment. Remarkably, Kin4 becomes dispensable for SPOC function in the absence of FEAR. Cells lacking both FEAR and Kin4 show that FEAR contributes to mitotic exit through regulation of the SPOC component Bfa1 and the MEN kinase Cdc15. Furthermore, we uncover controls that specifically promote mitotic exit in the daughter cell compartment., The mitotic exit network (MEN) triggers mitotic exit and can be blocked by the spindle position checkpoint (SPOC). Here the authors show that SPOC kinase Kin4 counterbalances MEN activation by the Cdc fourteen early anaphase release (FEAR) network in the mother cell and that in the absence of FEAR mitotic exit requires daughter cell-confined factors.